Collective forces of tumor spheroids in three-dimensional biopolymer networks - Mark, Christoph; Grundy, Thomas J.; Strissel, Pamela; Böhringer, David; Grummel, Nadine; Gerum, Richard; Steinwachs, Julian; Hack, Carolin; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner; O'Neill, Geraldine M.; et al. (eLife, 2020)
We describe a method for quantifying the contractile forces that tumor spheroids collectively exert on highly nonlinear three-dimensional collagen networks. While three-dimensional traction force microscopy for single cells in a nonlinear matrix is computationally complex due to the variable cell shape, here we exploit the spherical symmetry of tumor spheroids to derive a scale-invariant relationship between spheroid contractility and the surrounding matrix deformations. This relationship allows us to directly translate the magnitude of matrix deformations to the total contractility of arbitrarily sized spheroids. We show that our method is accurate up to strains of 50% and remains valid even for irregularly shaped tissue samples when considering only the deformations in the far field. Finally, we demonstrate that collective forces of tumor spheroids reflect the contractility of individual cells for up to 1 hr after seeding, while collective forces on longer timescales are guided by mechanical feedback from the extracellular matrix.
CRIS-Team WoS Importer:2020-05-22